WEAR DYNAMICS ANALYSIS OF THE SUPPORTING STRUCTURES OF SHUNTING LOCOMOTIVES OF INDUSTRIAL RAILWAY TRANSPORT UNDER THE INFLUENCE OF MATERIAL CORROSION - Horobets, Y. V (Science and Transport Progress, 2021)
Purpose. The research is aimed at obtaining new knowledge about the environmental influence on the supporting structures of the traction rolling stock of railways according to the corrosive wear parameter, the nature of the dynamics of this influence, as well as the evaluation of technical condition of the domestic traction rolling stock of industrial railways. Methodology. To obtain the relevant data, the author conducted aggregation and analysis of the results of ultrasonic thickness measurement of the main supporting structures of locomotives, obtained during eight years of the work to extend the service life of industrial transport locomotives. The supporting structures of series of locomotives presented in this study have a total range of service life of 25-48 years. They are located in different regions of Ukraine. Findings. The author found that among the surveyed fleet of diesel locomotives of industrial transport, the uniform corrosion level of supporting structures has a linear dependence on their service life with a rather low slope. Thus, according to the definitions of the normative documentation, which was relevant at the time of production of the rolling stock units that are the objects of this study, the material of the supporting structures (except for one particular case) belongs to the resistant group of metal corrosion resistance. Originality. Due to reasons such as the independence of industrial rolling stock from state-owned railway enterprises and the performance of maintenance work by various organizations, information on the general condition of the rolling stock of industrial transport is not readily available. The author for the first time collected statistical data on the state of industrial rolling stock and analyzed them. Practical value. The obtained results illustrate the development dynamics of equal corrosion of traction industrial transport structures, which, in turn, gives grounds for the subsequent improvement of the methodology of examining rolling stock units both during scheduled work and in order to extend the service life.